Causes of Iris Depigmentation in Young and Middle Age. Clinical Example - V. N. Trubilin; E. G. Poluninа; K. V. Chinenova; D. V. Andzhelova; V. V. Kurenkov; S. G. Kapkova (Oftalʹmologiâ)
The spontaneous change of eyes’ color is a quite rare complain in ophthalmological clinical practice for young and middle-aged patients. We consulted the 18-year-old patient complained that a month ago she noticed a change of the iris’ color. It was symmetrical in both eyes, which had lightened and acquired a “spotty appearance”. Before the appearance of these complaints, the patient had eyes of a rich dark brown color. After a comprehensive examination, the bilateral acute iris depigmentation (BADI) was diagnosed. BADI is bilateral symmetrical iris depigmentation followed by focal or diffuse stromal atrophy and pigment dispersion in the anterior segment. It is more common for young and middle-aged women, and is often asymptomatic. BADI has bilateral symmetrical iris depigmentation followed by focal or diffuse stromal atrophy and pigment dispersion in the anterior eye segment of the eye, which may affect the trabecular network. A feature of this disease is the absence of transillumination, changes in the shape of the pupil, and an inflammatory reaction. In some cases, repigmentation may occur spontaneously during the next few years. Therefore, from a prognostic point this disease has a favorable prognosis. However, patients with BADI syndrome should undergo regular ophthalmological examinations, including measurement of intraocular pressure to exclude the development of secondary open-angle pigmented glaucoma, and use sunglasses when the sun is bright. BADI syndrome must be differentiated with the following diseases: Fuchs heterochromic iridocyclitis, viral iridocyclitis caused by HSV and CMV, pigment dispersion syndrome and pseudo exfoliative glaucoma, as well as bilateral acute iris transillumination (BAIT) syndrome to make a correct diagnosis and apply adequate treatment tactics.